Pembaharuan Hukum Perkawinan Campuran di Indonesia - Jekalaya, I Wayan; Suradigama, I Wayan; Suartini, Made (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2024)
Legal relations in Civil Law give rise to legal protection for the parties based on applicable law. Civil law is a set of norms that regulate human relations between the parties themselves and with humans who have an interest in them. Humans have the right to marriage which is reflected in the Civil Code, the 1945 Constitution, and the other Law concerning about Marriage. With the issuance of statutory regulations governing marriage is a manifestation The state pays attention to legal relations, especially marriage, the problem is how to implement mixed marriages in a norm in order to realize legal objectives such as providing justice, legal certainty and benefits. Type of normative legal research, using normative case studies in the form of legal behavior products. The main point of the study is that law is conceptualized as a norm that applies in society and becomes a reference for everyone's behavior. The conclusion of the discussion in this article is that mixed marriages between Indonesian citizens and foreign citizens are permitted and legal according to the laws in force in Indonesia regarding the citizenship status of husband and wife being able to maintain their citizenship.